Web-Based Dietary and Physical Activity Intervention Programs for Patients With Hypertension: Scoping Review - Baderol Allam, Fatimah Najihah; Ab Hamid, Mohd Ramadan; Buhari, Siti Sabariah; Md Noor, Harrinni (JMIR Publications, 2021)
BackgroundHypertension is the root cause of many chronic diseases. Lifestyle changes (ie, dietary alterations and physical activity) are seen to be an important step in the prevention and treatment of hypertension. Educating people through web-based interventional programs could offer an effective solution and help these patients with hypertension in the existing health care scenario. ObjectiveIn this study, the researchers conducted a scoping literature review of the web-based dietary changes and physical activity-related intervention programs designed for the patients with hypertension and identified the methodologies, effectiveness, protocols, and theories, which could affect and improve existing clinical activities. MethodsThis review followed the scoping review methodology to identify and process the peer-reviewed studies published between 2010 and 2020. The literature searches were conducted on the following electronic databases: PubMed, Web of Science, MEDLINE (Medical Literature Analysis and Retrieval System Online), ScienceDirect, Scopus, and Google Scholar. By using relevant search terms, studies were included if they offered information related to the web-based intervention tools, specifically dietary and physical activity intervention for patients with hypertension. Studies written or translated in English language and published within the date range (January 2010 to March 2020) were included. ResultsOverall, 1441 articles were initially identified. The reviewers included 35 articles after removing duplicates and screening titles. Only 21 articles were assessed for full review, and 15 were kept for analysis. The researchers selected 15 web-based intervention articles published on the topic of hypertension from 7 countries. A few of these 15 web-based tools (4, 27%) included more than 3 functions and provided a lot of important information (such as appointments, health records, or viewable care). Several tools were standalone tools (11, 73%), while most of the tools supported communication intervention-related lifestyle or behavioral changes (13, 87%) and medication adherence (6, 40%). It was found that physicians (9, 60%), allied health professionals (5, 33%), and nurses (5, 33%) were the health care providers who generally used these tools for communicating with their patients. More than half of the above tools (10, 67%) were assessed by different researchers in randomized controlled trials, while 5 tools (33%) were investigated in nonrandomized studies. ConclusionsWe identified many web-based intervention programs for patients with hypertension from the literature databases. The findings indicate that numerous benefits can be derived after using a web-based dietary and physical activity intervention program for hypertension focusing on lifestyle changes. However, developers need to consider the preferences of the patients with regard to the information or the design features while developing or modifying web-based educational websites. These tools could be used for designing a patient-tailored website intervention program that is based on diet and physical activities for patients with hypertension.